Van Dyck and his age. - Brown, Christopher; Lev, Nilly; Lurie, Aya; Lurie, Doron J.; Omer, Mordechai (Tel Aviv : Tel Aviv Museum of Art Tel Aviv, 1995)
Van Dyck, Anthony ; Claeissens, Pieter ; Sellaer, Vincent ; de Backer, Jacob ; Pourbus, Frans ; Gheeraerts Jr., Marcus ; Rubens, Pieter Paul ; van Balen, Hendrick ; Brueghel, Jan ; Sustermans, Justus ; Voet, Jacob-Verdinand ; van Honthorst, Gerard ; Bril, Paul ; van Steenwyck Jr., Hendrick ; Teniers Jr., David ; van Verendael, Nicolaes ; Flinck, Govaert ; Maes, Nicolaas ; Netscher, Caspar ; Lely, Peter ; Kneller, Godfried ; Reynolds, Joshua ; Romney, George ; Hoppner, John ; Lawrence, Thomas
Biografie
Engels
boek
Keywords: Engeland; Vlaanderen